Executive Function, Motor Cordination and Body Composition in Childhood: the hole of sport pratice (Research, Society and Development, 2020)
The aim of this study was to verify the influences of the individual and collective sports practice on body composition, motor coordination, attention and executive function. The study included 85 students from public and private schools in the city of Brasília, in the Federal district with ages ranging from 7 to 11 years, being 41 practitioners of individual sports modalities and 28 non-practitioners of sports. Attention and executive function were evaluated by cancellation and f trails A and B tests (applied collectively). The Körperkoordination für Kinder (KTK) test was applied to evaluate the motor coordination. Results of the present study demonstrated that the practice of sport was not sufficient to provoke alterations on body composition. However, children who practice collective and individual sports obtained better motor coordination and capacity of executive function in relation to non-practicing children. Only the group of children of individual sports had higher results of cognitive flexibility and cognitive processing speed compared to the control group, no differences were evidenced between groups of collective sport and Individual in any variable. Therefore, sports practice demonstrated a potential role in motor coordination and executive function.